简体   繁体   中英

Summation of Selection Sort

I'm working through the algorithm design manual and stuck on understanding the summation behind selection sort in Chapter 2.

  1. Can someone explain how this summation is simplifed? For example, How do we get to n - i - 1?

  2. if n = 8, then s(n) is (8 - 1) + (8 - 2) + (8 - 3) etc. What does the result of this mean in relation to the formula? I've included a screenshot of the paragrah and my notes for context. screenshot of selection sort

\sum_{i=0}^{j-1} \sum_{j=i+1}^{n-1} 1 = \sum_{i=0}^{j-1} n - i - 1 , why this, where is j ?

You were asking about the simplifying step with which the index j is summed over. This link goes more in detail, but in general,

\sum_{j=u}^{v} 1 = -u + v + 1

is equivalent to this pseudo-code,

sum = 0
for(int j = u; j <= v; j++)
    sum += (f(j) = 1)
return sum

For example, with u=3 and v=22 , it would be sum = u - v + 1 = 22 - 3 + 1 = 20 .

图形表示。

With -u + v + 1 at u = i+1 and v = n-1 it simplifies to -(i+1) + (n-1) + 1 = n - i - 1 .

if n=8 does \sum_{i=0}^{n-1} n - i - 1 refer to (8-1) + (8-2) + (8-3) + ... + 2 + 1 [+ 0] , why two different kinds of values?

It has been simplified from (8-0-1) + (8-1-1) + (8-2-1) + ... (8-5-1) + (8-6-1) + (8-7-1) .

The technical post webpages of this site follow the CC BY-SA 4.0 protocol. If you need to reprint, please indicate the site URL or the original address.Any question please contact:yoyou2525@163.com.

 
粤ICP备18138465号  © 2020-2024 STACKOOM.COM